Reduction Disintegration Behavior and Mechanism of Vanadium–Titanium Magnetite Pellets During Hydrogen-Based Reduction - Feng Chen; Hao Li; Shuai Wang; Mao Chen; Wenbo Tang; Yufeng Guo; Yuekai Wen; Lingzhi Yang (Metals)
Hydrogen-based reduction followed by the electric furnace smelting of vanadium–titanium magnetite pellets offers notable advantages, including high reduction efficiency, reduced energy consumption, lower CO2 emissions, and improved titanium recovery. However, the disintegration of pellets during the reduction process presents a major barrier to industrial application. In this study, the reduction disintegration behavior and underlying mechanisms under hydrogen-based conditions were systematically investigated. The most severe disintegration was observed at 500 °C in an atmosphere of H2/(H2 + CO) = 0.25, where titano–magnetite [(Fe,Ti)3O4] was identified as the dominant phase. The complete transformation from titano–hematite [(Fe,Ti)2O3] to titano–magnetite occurred within 30 min of reduction. Extended reduction (60 min) further intensified disintegration (RDI−0.5mm = 81.75%) without the formation of metallic iron. Microstructural analysis revealed that the disintegration was primarily driven by volumetric expansion resulting from the significant increase in the titanium–iron oxide unit cell volume. Raising the reduction temperature facilitated the formation of metallic iron and suppressed disintegration. These findings provide essential guidance for optimizing reduction parameters to minimize structural degradation during the hydrogen-based reduction of vanadium–titanium magnetite pellets.